The levels and impacting factors of serum amyloid A in the acute exacerbation of allergic asthma - Yan-Wen CUI; Li-Hui WANG; Chun-Xian DU; Ya-Dong GAO (Yixue xinzhi zazhi)
Objective To analyze the expression levels of serum amyloid A (SAA) in patients with allergic and non-allergic asthma, and explore the correlation between SAA and acute exacerbation severity and identify biomarkers of allergic asthma.Methods Asthmatic patients treated in the Department of Respiratory and Critical Care Medicine, Zhongnan Hospital of Wuhan University from 2018 to 2019 were collected and divided into allergic asthma and non-allergic asthma groups according to the allergen test results. The SAA levels of the two groups of patients were then compared. The correlation between total IgE, FeNO, EOS and allergen-specific IgE levels were analysed. Logistic regression analysis was used to explore the relationship between SAA and allergic asthma.Results A total of 127 patients were included in study, with an average age of 50.5±16.6 years, of which 69 (54.3%) were female, 57 patients had allergic asthma and 70 had non-allergic asthma. Patients with allergic asthma had significantly higher SAA levels than those with non-allergic asthma [(26.8±27.4) mg/L vs. (9.1±5.8) mg/L)]. The level of SAA in patients with severe to severe acute allergic asthma was (55.0±16.4) mg/L, which was significantly higher than that in patients with mild to moderate acute allergic asthma (13.8±13.0) mg/L. SAA level in allergic asthma patients was positively correlated with levels of allergen sIgE (r=0.398, P=0.044). There were no correlations between SAA and total IgE, FeNO and EOS%. SAA (OR=1.138, P